Fabrication and effect of applied field stresses on stability of ZnO ceramics with CaMnO₃ as additive for varistor application - Lakin, Ismail Ibrahim (2015)
The major challenge in the continuing development of varistor has been to reduce the energy loss which is due to temperature and applied field stresses and to attain a good stability. The aims of this study are; to study the effect of CaMnO3 (CMO) contents on nonlinearity coefficient (α) enhancement of ZnO based varistor ceramics; and secondly to study the nonlinear stability of this ceramic against DC electrical field and thermal stresses as function of CMO contents. The first aim has been carried out by synthesis of ZnO + xCMO ceramics by citrate gel coating technique, where x ranging from 3 – 7 mol% and sintered at various sintering times from 1 – 3 hrs. The prepared samples were characterized by using TG/DTA, EDX, SEM, XRD, and I-V measurements. The second aim was carried out by choosing the samples with best electrical properties subjecting them simultaneously to stresses of specific temperature and DC voltage over a certain period of time to study the degree of degradation. XRD analysis shows that the main phase in the material systems was ZnO while CMO as the secondary phase increase gradually with the increase of mol%, x. The TG/DTA analysis shows that, good quality of ZnO-CMO can be achieved at calcination temperature above 650 °C. Average density of the ceramics in all systems has the same trend where it decreases with the increase of doping level and sintering time. The maximum grain size was found to be 23.4 μm at the highest sintering time at 3 hrs at 7 mol% CMO doping level, as Mn is a strong grain enhancer. The SEM and EDX results verified that Ca and Mn were distributed within the grain as well as in the grain boundaries and triple point junctions. The value of α was found to increase with amount of CMO up to 5 mol% concentration. An optimum sintering time of 3 hrs for 5 mol% doping level gave the best α, attaining a value of 42.3 which represent a high protective function of ZnO varistor. The DC stress has caused a decrease in varistor voltage, α, and also an increase in leakage current. After exposure to DC and heat stresses for 18 hours, the varistor ceramics experienced a slight drop in nonlinearity. Thus, the varistor ceramic samples exhibited a high level of leakage current compared to samples before degradation which indicated they have been degraded or deteriorated. The degradation percentage was calculated in terms of changes in varistor parameters before and after stress. It showed that sample with 3 mol% CMO possess lowest degradation percentage. From this result, it was found that samples fabricated at 3 hrs sintering time have the best microstructure and electrical properties.